Analisis Efektivitas Kontribusi Pajak Daerah Dan Retribusi Daerah Sebagai Sumber Pendapatan Asli Daerah Kabupaten Lembata Provinsi Nusa Tenggara Timur Tahun 2017–2020 - Agustina T.C. Bediona; Muhammad Taufiq Hidayat (Universitas Dian Nuswantoro, 2022)
This study aims to (1) analyze the level of local tax contributions and local tax levies as a source of PAD for Lembata Regency, East Nusa Tenggara Province in 2017 – 2020, which have been effective, (2) Find out local taxes and regional levies as a source for Lembata Regency, East Nusa Tenggara Province in 2017-2020. 2017 – 2020 have contributed. This study uses a quantitative descriptive analysis method. The data used is secondary data. In the form of a report on the realization of regional tax revenues for Lembata Regency.The results of this study indicate that (1) The level of effectiveness of Regional Tax Contributions and Regional Levies as a source of PAD in Lembata Regency in the 2017 fiscal year range has a percentage value of 100.39%, in the 2018 fiscal year range it has a percentage value of 120.87%, in the 2019 range has a percentage value of 152.76%, and in the 2020 fiscal year range it has a percentage value of 568.64%. So it can be drawn that the average percentage of effectiveness has a percentage value of 235.66%, which means that the level of effectiveness of the contribution of local taxes and regional levies in Lembata Regency has a very effective effectiveness value. (2) The contribution of local taxes and regional levies towards increasing PAD in Lembata Regency is included in the very effective category. The contribution of local taxes and regional levies in Lembata Regency in 2017 to 2020 is 51.15%, 50.53%, 40.39%, 62.79%. So it is drawn that the average Regional Tax Contribution and Regional Levies for Lembata Regency reaches 51.21% so that it can be categorized as very good.